No longer in denial [network security]. - Comerford, R. (IEEE spectrum)
The world was made rudely aware of the battle between hackers and Internet system security administration when public access to the sites of Amazon, eBay, Yahoo!, and other dot-coms was cut off by a new method of attack called distributed denial of service (DDoS), in February 2000. To block the sites, one or more hackers sneaked into the computers of several unsuspecting users connected to the Net, and used these widely dispersed machines as drones to launch a barrage of false messages. DDoS is a network problem because it abuses the network's resources; so the solution has to be in the network. Security experts are planning to fight the war with DDoS hackers on many fronts-from the Web-server vanguard through to the personal computers in the trenches. In the wake of the February attack, their first act has been to try to establish lines of communications among Web site operators, Internet service providers (ISPs), and legal authorities. The work of the Internet Engineering Task Force in tacking the hacker by tracking the flow of data packets through the network